2023
DOI: 10.3389/fcimb.2023.1038472
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional effects of oral anticoagulants on gut microbiota in patients with atrial fibrillation

Abstract: BackgroundThe imbalance of gut microbiota (GM) is associated with a higher risk of thrombosis in patients with atrial fibrillation (AF). Oral anticoagulants (OACs) have been found to significantly reduce the risk of thromboembolism and increase the risk of bleeding. However, the OAC-induced alterations in gut microbiota in patients with AF remain elusive.MethodsIn this study, the microbial composition in 42 AF patients who received long-term OAC treatment (AF-OAC group), 47 AF patients who did not (AF group), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…In a separate study, Li et al observed that oral anticoagulants (OACs) altered the composition of gut microbiota, speci cally increasing the abundance of Megamonas and decreasing pro-in ammatory colonies in patients with atrial brillation (AF). This shift in microbiota was associated with reduced thrombosis and highlighted the potential modulatory role of Megamonas in abnormal lipid metabolism [ 57]. In conclusion, our ndings reinforce the aforementioned conclusions and identify novel therapeutic targets for the management of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 83%
“…In a separate study, Li et al observed that oral anticoagulants (OACs) altered the composition of gut microbiota, speci cally increasing the abundance of Megamonas and decreasing pro-in ammatory colonies in patients with atrial brillation (AF). This shift in microbiota was associated with reduced thrombosis and highlighted the potential modulatory role of Megamonas in abnormal lipid metabolism [ 57]. In conclusion, our ndings reinforce the aforementioned conclusions and identify novel therapeutic targets for the management of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 83%
“…Intestinal flora might have an indirect effect on OACs through the metabolites generated, or a direct effect on vitamin K-producing bacteria and structural modifications of drug molecules. Correspondingly, Li et al [ 134 ] demonstrated that the implementation of OACs in AF patients might mitigate inflammation, atherosclerosis, and thrombosis by altering the abundance of gut microbiota. Nonetheless, OACs might raise the risk of bleeding in the gastrointestinal tract and other parts of the body through certain potential pathogens.…”
Section: Therapeutic Potentials For Modulating the Microbiomementioning
confidence: 99%